Imam Abu Hanifah sebagai Ulama Hadis dan Imam Mazhab dalam Pandangan Abdul Fattah Abu Ghuddah - Adi Abdullah Muslim (AQWAL Journal of Qur'an and Hadis Studies, 2021)
The study of classical book tahqiq is attached to the figure of a hadith scholar named Abdul Fattah Abu Ghuddah. This is because the research he has done has studied and commented on the works of classical scholars, who showed their attention to the treasures of past scholarship. In commenting on the studies researched him, the hadiths, interpretations, moral fiqh and others do not show his inclination towards the school that he holds. The scholarly figure of Abdul Fattah Abu Ghuddah in the field of hadith who adheres to the Imam Abu Hanifah school of thought does not make it necessary to quote all his tahqiq works from scholars of the Imam Abu Hanifah school of thought. As a behavior that maintains the scientific tradition of past scholars. However, there were times when Abdul Fattah Abu Ghuddah commented on the classical scholars' criticism of Imam Abu Hanifah's character in the field of hadith. This discussion is reviewed in several books that are tahqiq. This research is a qualitative research with a historical approach through descriptive analysis method